(untitled) (Journal of Pharmaceutical Negative Results, 2022)
From the rare species that cause urinary tract infections, seven different types of coagulation-negative Staphylococcus bacteria were isolated (9.82%) Staphylococcus epidermidis (8.9%) Staphelococcus haemolyticus, (3%) Staphylococcus xylosus (0.89%) for each bacteria Staphylococcus auricularis, Staphylococcus simulans, Staphylococcus hominis, and Staphylococcus lugduensis, as all isolates were 100% producers of biofilms by tube method and (40%) of Congo Red by Staphelococcus. haemolyticus, while the rest of the species were not producers by the Congo Red method and all isolates were fully resistant to the antibiotics. Amoxicillin/Clavulanic Acid, Oxacillin, Cefotaxim, Cefepime, Levofloxacin, and in a high percentage of cases highly sensitivite to the antibiotics Rifampcin and Amikacin.